(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Purpose: This study applied the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) to examine factors influencing the adoption of OTT platforms among youth in Navsari city, India. With the growing popularity of OTT platforms, understanding their key adoption determinants can help service providers enhance user engagement and satisfaction. Design/methodology/approach: A quantitative research approach was employed, using a structured questionnaire to collect data from 211 youth respondents. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to analyze relationships among constructs and assess the model’s predictive power. Findings: Results indicate that Facilitating Conditions (FC), Habit (H), and Price Value (PV) significantly influence behavioral intention and actual OTT usage. Facilitating Conditions (FC) emerged as the strongest predictor, emphasizing the role of accessibility and resources. However, Effort Expectancy (EE), Performance Expectancy (PE), Social Influence (SI), and Hedonic Motivation (HM) did not significantly affect behavioral intention. The Q²predict values for Behavior (0.479) and Behavioral Intention (0.449) confirm good predictive relevance. Practical implications: OTT providers should enhance accessibility, affordability, and user engagement. Personalized recommendations, seamless user experience, and cost-effective subscription models can further boost adoption among youth. Originality/value: This study applies UTAUT2 in OTT adoption research, contributing to technology acceptance literature. The finding that EE, PE, SI, and HM do not significantly influence behavioral intention contrasts with previous studies, opening avenues for further research.